Morphological Analysis on the Language Acquisition - Waad Dawood Naser; Nilotpala Gandhi (Journal La Sociale, 2022)
The paper highlights the importance of Morphology in Linguistics and in the acquisition of new language. It outlines various elements forming the domain of morphology in brief and its role in learning of a new language in detail. Language acquisition is an interesting topic studied by most linguists from the time of inception of language learning as a cognitive science. The topic is still frequently studied by linguistic enthusiasts especially through the lens of morphological analysis. It is a secondary research paper.